Variations and Environmental Controls of Primary Productivity in the Amundsen Sea - Feng, Jianlong; Li, Delei; Zhang, Jing; Zhao, Liang (Frontiers in Marine Science, 2022)
The Amundsen Sea is one of the regions with the highest primary productivity in the Antarctic. To better understand the role of the Southern Ocean in the global carbon cycle and in climate regulation, a better understanding of the variations and environmental controls of primary productivity is needed. Using cluster analysis, the Amundsen Sea was divided into nine bioregions. The biophysical differences among bioregions enhanced confidence to identify priorities and regions to study the temporal and spatial variations in primary productivity. Four nearshore bioregions with high net primary productivity or rapidly increasing rates were selected to analyze temporal and spatial variations in primary productivity in the Amundsen Sea. Due to changes in net solar radiation and sea ice, primary production had significant seasonal variation in these four bioregions. The phenology had changed at two bioregions (6 and 7), which has the third and fourth highest primary production, due to changes in the dissolved iron. Annual primary production showed increasing trends in these four bioregions, and it was significant at three bioregions. The variation in primary production in the bioregion (9), which has the highest primary production, was mainly affected by variations in sea surface temperatures. In the bioregion (8), which has the second-highest primary production, the primary production was significantly positively correlated with sea surface temperature and significantly negatively correlated with sea ice thickness. The long-term changes of primary productivity in bioregions 6 and 7 were thought to be related to changes in the dissolved iron, and dissolved iron was the limiting factor in these two bioregions. Bioregionalization not only disentangles multiple factors that control the spatial differences, but also disentangles limiting factors that affect the phenology, decadal and long-term changes in primary productivity.